Building Structured Peer-to-Peer Resource Sharing Platform Using Object Encapsulation Approach - Shufang ZHANG; Jun HAN (Institute of Advanced Engineering and Science, 2013)
This paper designed and built a distributed hash table based computing resource sharing platform named OE-P2RSP. By employing Peer-to-Peer services, OE-P2RSP allowed users to submit jobs to be run in the system and to run jobs submitted by other users on any resources available over the Internet, essentially allowing a group of users to form an Ad hoc set of shared resources. OE-P2RSP is based on structured peer on network share, improves the communication mode of system by encapsulated object, object group, and physical proximity principle, and the use of physical proximity principle, and gathers computing resources better in the same research institution or enterprise within local area network. The experimental results obtained via simulations show that the system can reliably execute scientific applications on a widely distributed set of resources with good load balancing and low matchmaking cost and that OE-P2RSP has good efficiency, load balancing and scalability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2056